2016
DOI: 10.1016/j.ajo.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of 27 Gauge Microincision Vitrectomy Surgery for Posterior Segment Disease

Abstract: The 27 gauge PPV was well tolerated with low rates of intraoperative and postoperative complications across varied surgical indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 39 publications
6
68
2
1
Order By: Relevance
“…The decreased vitreous flow rate or so-called “cutting efficiency” observed with those smaller 27-gauge instruments was at least partially overcome by the development of higher cutting speed devices and high aspiration levels along with duty cycle improvements (described in next sections) that are already present on some of the commercially available platforms [7, 14, 19, 20]. In a recent publication, the mean operative time was similar to the initial reports using the 23-gauge instruments, regardless the potentially reduced flow rate [12].
Fig.
…”
Section: Vitrectomy Cuttersmentioning
confidence: 53%
See 3 more Smart Citations
“…The decreased vitreous flow rate or so-called “cutting efficiency” observed with those smaller 27-gauge instruments was at least partially overcome by the development of higher cutting speed devices and high aspiration levels along with duty cycle improvements (described in next sections) that are already present on some of the commercially available platforms [7, 14, 19, 20]. In a recent publication, the mean operative time was similar to the initial reports using the 23-gauge instruments, regardless the potentially reduced flow rate [12].
Fig.
…”
Section: Vitrectomy Cuttersmentioning
confidence: 53%
“…Subsequent years have shown that the modern MIVS have numerous advantages over 20-gauge vitrectomy and are associated with better patient comfort, less conjunctival scarring, less postoperative inflammation and earlier visual recovery [711]. More recently, 27-gauge instruments released by different companies have shown encouraging results [79, 12, 13]. …”
Section: Vitrectomy Cuttersmentioning
confidence: 99%
See 2 more Smart Citations
“…One-step trocar insertion perpendicular to the pars plana is preferred to angled insertion leading to less instrumentation bending. This wound construction approach also results in a low rate of complications; no cas- es of postoperative hypotony and few cases of sclerotomy suturing have been reported [1,2]. Trocars are inserted closer to the 9 and 3 o'clock positions, allowing better access to the 12 o'clock peripheral vitreous.…”
Section: Introductionmentioning
confidence: 99%